Pengaruh Bimbingan Kelompok Teknik Problem Solving Terhadap Kedisiplinan Belajar Siswa Kelas XI MIPA Di SMA Islam Sultan Agung 1 Semarang - Laras Budiansyah; Retnaningdyastuti Retnaningdyastuti; Primaningrum Dian (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The research was motivated by several problems, namely: (1) students violated time discipline, namely: late coming to school, truant and late submitting assignments; and (2) students commit disciplinary violations, namely: not participating in ceremonies, wearing incomplete attributes, sleeping in class, quarreling at school, playing cellphones during class, falsifying picket attendance data, and violating the use of attributes. The purpose of the study was to determine the influence of group guidance on problem solving techniques on student learning discipline. This research uses a quantitative approach with a quasi-experimental design with a nonequivalent control group design model. The research population of all class XI MIPA students at Sultan Agung Islamic High School 1 Semarang amounted to 72 students. The research sample was 35 students of grade XI MIPA 2 at Sultan Agung 1 Islamic High School Semarang. The sampling technique uses cluster random sampling. Psychological scale data collection techniques. Data analysis techniques use descriptive statistics. Test the hypothesis of simple linear regression. The results of the study showed the influence of group guidance with problem solving techniques on student learning discipline. The influence provided by group guidance services with problem solving techniques on the learning discipline of grade XI MIPA students at Sultan Agung Islamic High School 1 Semarang obtained an R-Square value of 0.38, group guidance services with problem solving techniques had an influence of 38%. There is an influence of group guidance with problem solving techniques on the learning discipline of grade XI MIPA students at Sultan Agung Islamic High School 1 Semarang.